Management Challenges in Implementing the Merdeka Curriculum - Nur ‘Azah; Muh Ibnu Sholeh; Sahri Sahri; Bambang Wahrudin; Hawwin Muzakki (Al-Hayat: Journal of Islamic Education, 2024)
This study focuses on implementing the Merdeka curriculum from the perspective of its management challenges, exploring the experiences and perceptions of stakeholders related to implementing the Merdeka Curriculum at MAN Jombang and using a qualitative study, interviews, observations, and documentation as data collection techniques. Data analysis used data reduction, coding, and theme identification stages. To ensure data validity, the researcher applied source triangulation. The study findings indicate that implementing the Merdeka Curriculum faces challenges related to technology access and teacher readiness. Technology limitations, including unequal access to devices, hinder effective project-based learning, and administrative staff acknowledge the need for infrastructure improvements. Students appreciate the curriculum's focus on personal interests but need more guidance to navigate independent learning. Teachers have received training in project-based learning, but many teachers need help implementing new methods effectively. Although progress has been made, continued support, increased resources, and collaborative efforts among stakeholders are critical to successfully implementing the Merdeka Curriculum and improving educational outcomes. Limitations of the study include limited observation time and potential bias in participant responses. This study has yet to explore the long-term impacts of implementing the Merdeka Curriculum. Stakeholder collaboration research can provide deeper insights into practical strategies to address challenges and improve educational outcomes in Islamic education.